Pengaruh Online Customer Rating, Word of Mouth dan Iklan E-commerce terhadap Minat Beli Pakaian pada Marketplace TikTok dalam Perspektif Islam - Surahmah, Surahmah; Hariani, Mila (Institut Agama Islam YPBWI Surabaya, 2024)
This research aims to analyze the influence of online customer ratings, word of mouth, and e-commerce advertising on interest in buying clothes on the TikTok marketplace from an Islamic perspective. The research method used is qualitative with a primary and secondary data approach. The objects in this research are TikTok users who have purchased clothes on the TikTok marketplace. The data collection technique in this research is primary data obtained through online questionnaires distributed to respondents, while secondary data is obtained from literature studies, journals and other relevant sources. The research results show that online customer ratings, word of mouth, and e-commerce advertising simultaneously have a significant effect on interest in buying clothes on the TikTok marketplace. From an Islamic perspective, online customer assessment and word of mouth promotion are in line with the principles of transparency and honesty, while e-commerce advertising must pay attention to aspects that are not deceptive and do not contain prohibited elements. The implication of this research is the need for TikTok market managers to improve the quality of online customer assessments and encourage positive word of mouth, as well as designing e-commerce advertisements that are in accordance with Islamic principles.